Kecakapan Hidup Pribadi Terhadap Anak dalam Antologi Wacan Bocah “Sithik Eding” Karya Zuly Kristanto - Salsabila Hamami; Latif Nur Hasan (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
Life skills education is learning about the skills a person has to help deal with problems in life to integrate with the surrounding environment in any condition to help improve his quality of life. Anthology Wacan Bocah Sithik Eding is a children's storybook that uses Javanese language and there are lessons for children to learn. This research aims to explain personal life skills and describe personal life skills in the Anthology of Wacan Bocah. The method used is the qualitative method which explains the statement with description. The data source in this research is Anthology Wacan Bocah Sithik Eding. The data in this research are sentences extracted from the Wacan Bocah Sithik Eding. The instruments used are the researcher himself and the book Anthology of Wacan Bocah Sithik Eding. How to collect data by reading the wacan bocah, recording the data, and classifying the data. The method of data analysis used is reading the wacan bocah from beginning to end, classifying the data, and recording the data in the research. The results of the research is describe personal life skills education for children in the anthology of wacan bocah Sithik Eding. Personal life skills are self-awareness, rational thinking, and confidence.